PERANCANGAN DATABASE SISTEM INFORMASI AKUNTANS MENGGUNAKAN KOMBINASI REA MODEL, ERD, DAN NORMALISASI DATA - Michael Iskandar; Christian C. Henry; Asdi Aulia (Bina Ekonomi, 2011)
In the field of accounting, information technology becomes the standard tool of the trade. It allows for much more accurate and faster processing of accounting data, while keeping costs down. These advantages require accountants to understand the basics of information technology related to information processing.  One of the most important is the knowledge about database design, in which comprehension will ensure that all necessary data for financial statements are captured and business rules are adhered to. This paper discusses a database design method which combines the data normalization process, entity- relationship approach and resources-events- agents’ model.